THE DIRECTOR'S STRATEGY IN BUILDING A THEATER OF MIND ON THE P.O.V. EPISODES OF RADIO FEATURE PROGRAM MINIMAL-IS-ME - Heriyanto Heriyanto; Prasasti Dharma Adi Negoro (International Journal Labs, 2022)
Background: The production of this radio feature work focuses on providing options for young people to overcome financial problems that have an impact on psychology by applying a lifestyle of minimalism, in addition to the history of minimalism and the direct story of people who apply minimalism in everyday life. minimalism lifestyle is one way to overcome the overconsumption lifestyle that exists in society. Objective: The purpose of creating this production work was to produce a radio feature work with the title